A comparison of quadratic programming solvers in support vector machines training - Zaki, N. M. (Penerbit UTM Press, 2003)
Training a Support Vector Machine requires the solution of a very large quadratic programming problem. In order to study the influence of a particular quadratic programming solver on the Support Vector Machine, three different quadratic programming solvers are used to perform the Support Vector Machine training. The performance of these solvers in term of execution time and quality of the solutions are analyzed and compared. A practical method to reduce the training time is investigated.